STUDI KANDUNGAN KARAGINAN RUMPUT LAUT Kappaphycus sp. PADA UMUR PANEN YANG BERBEDA - Masthora, Siti; Abdiani, Ira Maya (Jurnal Harpodon Borneo, 2016)
The aim of this study was to know the content of carrageenan from harvesting seaweed (Kappaphchus alvarezii) with different ages. The research consists of 5 treatments of different levels of harvest age were 30 days, 37 days, 45 days, 52 days and 60 day. The observed parameter were yield, moisture content and ash content. Result showed the average value of the highest yield at harvest time 52 days was 61.87%, followed by successive harvest age of 60 days, 45 days, 37 days and 30 days with an average value of the yield were 60.67% , 60 , 60%, 59.00% and 58.67%. Value - average water content ranged from 7.33% to 10%, while the average value of the ash content ranging from 17% -18.33%. Based on the analysis of variance, the seaweed’s harvesting gave the significant of effect on the carrageenan’s content.Keywords: Kappaphycus sp., harvesting, content of carrageenan